Bacterial nitrate assimilation: gene distribution and regulation. (21st November 2011) - Luque-Almagro, Víctor M.; Gates, Andrew J.; Moreno-Vivián, Conrado; Ferguson, Stuart J.; Richardson, David J.; Roldán, M. Dolores
Abstract : In the context of the global nitrogen cycle, the importance of inorganic nitrate for the nutrition and growth of marine and freshwater autotrophic phytoplankton has long been recognized. In contrast, the utilization of nitrate by heterotrophic bacteria has historically received less attention because the primary role of these organisms has classically been considered to be the decomposition and mineralization of dissolved and particulate organic nitrogen. In the pre-genome sequence era, it was known that some, but not all, heterotrophic bacteria were capable of growth on nitrate as a sole nitrogen source. However, examination of currently available prokaryotic genome sequences suggests that assimilatory nitrate reductase (Nas) systems are widespread phylogenetically in bacterial and archaeal heterotrophs. Until now, regulation of nitrate assimilation has been mainly studied in cyanobacteria. In contrast, in heterotrophic bacterial strains, the study of nitrate assimilation regulation has been limited to Rhodobacter capsulatus, Klebsiella oxytoca, Azotobacter vinelandii and Bacillus subtilis . In Gram-negative bacteria, the nas genes are subjected to dual control: ammonia repression by the general nitrogen regulatory (Ntr) system and specific nitrate or nitrite induction. The Ntr system is widely distributed in bacteria, whereas the nitrate/nitrite-specific control is variable depending on the organism.